Encapsulation of Cinnamaldehyde using Chitosan: Stability, Mucoadhesive and Cinnamaldehyde Release - Purbowatiningrum Ria Sarjono; Ngadiwiyana Ngadiwiyana; Enny Fachriyah; Ismiyarto Ismiyarto; Nor Basid Adiwibawa Prasetya; Khikmah Khikmah (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2018)
Cinnamaldehyde contained in cinnamon oil is useful as an antidiabetic; however, it has very low oral bioavailability. One effort to increase oral bioavailability of cinnamaldehyde is by encapsulation using chitosan. Encapsulation of cinnamaldehyde in chitosan has been successfully made in the form of powder. The aim of this study was to obtain data of stability, mucoadhesive and cinnamaldehyde release from cinnamaldehyde encapsulated chitosan. Stability tests were performed physically and chemically. Mucoadhesive tests were carried out in vitro in two steps, which were granule fabrication and then mucoadhesive test. The results showed that the levels of cinnamaldehyde decreased within 4 weeks, from the first to the fourth week 100%; 99.87%; 98.85%; 97.33%, respectively. Cinnamaldehyde powder did not change significantly in specific gravity, pH, centrifugation and organoleptic after a month. The release precentage of cinnamaldehyde in acidic media pH 1.2 for 180 minutes was 83.4%, whereas in alkaline media pH 7.4 for 360 minutes was 61%. The cinnamaldehyde encapsulated chitosan nanoparticle powder performed mucoadhesive capacity in the gastric mucosa and in the intestinal mucosa of 91.5% and 84.61%, respectively.